2008
DOI: 10.1044/1059-0889(2008/006)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Room Acoustics and Sound-Field Amplification on Word Recognition Performance in Young Adult Listeners in Suboptimal Listening Conditions

Abstract: These results demonstrate how meeting the ANSI S12.60-2002 standard, which was written for elementary school classrooms, can benefit young adult listeners in postsecondary classrooms. Also, classroom amplification was shown to improve speech recognition for students across the classroom in both acoustically poor and acoustically sound classroom environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Where appropriate, modifications to heating/ventilation systems should be undertaken to reduce background noise levels and consideration of methods to reduce excessively long RTs should be considered for existing classrooms. However, if such modifications are not possible, sound-field amplification should be considered as a way of improv-ing the SNR in the classroom (Larsen et al, 2008). Both instructors and students should be made aware of the importance of good SNRs in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where appropriate, modifications to heating/ventilation systems should be undertaken to reduce background noise levels and consideration of methods to reduce excessively long RTs should be considered for existing classrooms. However, if such modifications are not possible, sound-field amplification should be considered as a way of improv-ing the SNR in the classroom (Larsen et al, 2008). Both instructors and students should be made aware of the importance of good SNRs in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to support the value of maintaining college classrooms that are in compliance with these standards. Larsen et al (2008) compared the word recognition of 53 college students in two classrooms differing in compliance with ANSI recommendations. Speech recognition performance in the classroom that met ANSI standards (RT 5 0.53 sec, background noise level 5 34 dBA, SNR ' 12 dB) was significantly better than performance in the classroom that did not meet ANSI recommended levels (RT 5 0.76 sec, background noise level 5 44 dBA, SNR ' 3 dB).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing words as a crucial factor for successful listening comprehension in second language development is continuously investigated by Larsen et al, (2008), Staehr (2009, Webb and Rodgers (2009a), Webb and Rodgers (2009b), Jafari and Hashim (2012); Van Zeeland and Schmitt (2013a), Schmitt (2013b), Yamamoto, (2014). However, less research has directly studied the role of word recognition from speech (WRS) in listening.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other tasks may be more difficult to carry out in the presence of classroom reverberation even without masking sounds. Larsen et al (2008) found that in the absence of amplification, college-aged participants were much less accurate in writing down CVC monosyllabic words played over speakers located in the front of a classroom that did not meet the ANSI standard for reverberation (44% accuracy) in comparison to one that did (82% accuracy). Moreover, especially in the high-reverberation classroom, word recognition performance degraded with distance from the sound source.…”
Section: Classroom Acoustics and The Perception Of Speech Soundsmentioning
confidence: 96%